Development of Smart Sensing Technology Approaches in Structural Health Monitoring of Bridge Structures. (20th August 2021) - Sivasuriyan, Arvindan; Vijayan, D. S.; LeemaRose, A.; Revathy, J.; Gayathri Monicka, S.; Adithya, U. R.; Jebasingh Daniel, J.
Abstract : In recent years, immense development in Structural Health Monitoring (SHM) of bridges helps address the life span and reliability of bridge structure at contrasting phases of their service life. This article provides a detailed understanding of bridge monitoring, and it focuses on sensors utilized and all kinds of damage detection (strain, displacement, acceleration, and temperature) according to bridge nature (scour, suspender failure, disconnection of bolt and cables, etc.) and environmental degradation under static and dynamic loading. This paper presents information about various methods, approaches, case studies, advanced technologies, real-time experiments, stimulated models, data acquisition, and predictive analysis. Future scope and research also discussed the implementation of SHM in bridges. The main aim of this research is to assist researchers in better understanding the monitoring mechanism in bridges.